Analisis Multivariat Kejadian Hipertensi di Masyarakat RW 009 Kelurahan Bojong Menteng dan Kelurahan Jati Luhur Bekasi Tahun 2018 (Analisis Data Sekunder) - Shinta Sari Dewi (UHAMKA Press, 2020)
Data from Puskesmas in Bekasi City show the number of hypertension sufferers is 12,545 people. Based on the highest prevalence of hypertension in Bekasi City, especially in the Bojong Menteng Village and Jati Luhur Village, researchers are interested in researching the incidence of hypertension. The purpose of this study was to determine the most dominant factor with the incidence of hypertension in the community of RW 009, Bojong Menteng, and Jati Luhur Bekasi in 2018 (secondary data analysis). This research is a quantitative study with a cross-sectional study design. The data used is secondary data on hypertension in 2018 with a sample size of 304 respondents and the sampling technique uses a saturated sampling method. Data analysis used a chi-square statistical test and multiple logistic regression. The incidence of hypertension in the community of RW 009, Bojong Menteng Village, and Jati Luhur Bekasi Village was 48.7%. The results of multivariate analysis showed that the most dominant variable with the incidence of hypertension was age with an OR value of 5.756. Suggestions for the community of RW 009 Kelurahan Bojong Menteng and Kelurahan Jati Luhur Bekasi are to regularly check their blood pressure at health facilities, have a healthy lifestyle, and be more active in physical activities.